LEST THE DEAD BURY THE LIVING: THE RELATIONSHIP OF HUMAN AND HISTORY IN FRIEDRICH NIETZSCHE - İBŞİROĞLU KOCAMAN, Çiğdem (SSD Journal, 2018)
In this study, the nexus of human and history is examined in line with Friedrich Nietzsche’s work of On the Advantage and Disadvantage of History for Life (2006). Within this context, firstly, why we need history, the importance of history for human life and how and from what points of view history should be approached according to Nietzsche, will be addressed. Then, it will be emphasized that it is possible for human, that live in past, the moment-now- and future, namely in the three dimensions of time, to live without remembering, but it is impossible to live without forgetting. On the other hand, how to determine the threshold where the "sense of history" held by a human or people or a cultural environment starts to harm, and where to seek for the meaning attached to history, will be probed in accordance with Nietzsche's three types of history conception as"monumental, antiquarian and critical history". The study, aiming to question about the understanding of 'the' history that will make human life more valuable, enrich it and serve for it, is concluded with Nietzsche's opinions on human with respect to their immediate relevance to history.